1994
DOI: 10.3109/00365529409094875
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Prescriptions for Peptic Ulcer Drugs (ACT Class AOB2) in Iceland

Abstract: The results of the survey suggest that the extensive use of peptic ulcer drugs in Iceland is mostly due to excessive use in non-ulcer dyspepsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…Despite this, studies such as this one indicate that there is widespread leakage outside the subsidized indications, particularly in the less severe forms of gastro‐oesophageal disease (25, 30, 31). Similar findings have been reported internationally (27, 32, 36).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite this, studies such as this one indicate that there is widespread leakage outside the subsidized indications, particularly in the less severe forms of gastro‐oesophageal disease (25, 30, 31). Similar findings have been reported internationally (27, 32, 36).…”
Section: Discussionsupporting
confidence: 92%
“…Despite this, studies such as this one indicate that there is widespread leakage outside the subsidized indications, particularly in the less severe forms of gastro-oesophageal disease (25,30,31). Similar ®ndings have been reported internationally (27,32,36). The results demonstrated that proton pump inhibitors were prescribed in accordance with the Australian Schedule of Pharmaceutical Bene®ts criteria in only slightly more than one-third the cases studied, a very similar ®nding from the recent study in Brisbane, which found only 31% met the same criteria (30).…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, we estimate that the present data reflect the use of antiasthma drugs at the time the survey was performed. The proportion of prescriptions from general practitioners and specialists was similar to the results of a previous study on the use of antiulcer drugs carried out in Iceland in April 1991 [7]. The response rate for the patients' questionnaires was higher in the present study, probably because, at the time of purchase, the option to post replies was available.…”
Section: Discussionsupporting
confidence: 75%
“…Although most, but not all, large well-conducted trials with potent acid secretion inhibitors show a better effect of these drugs than placebo, the overall difference is modest (9,10,12,13). The modest effect is in contrast to the widespread use of these drugs in patients with FD (15)(16)(17). However, with a multi-crossover method it has been shown that these drugs are highly effective in a subgroup of patients with FD, but it has not been possible to characterize the responders on the basis of symptoms or signs, and the multi-crossover method is not fit for daily practice (11).…”
Section: Discussionmentioning
confidence: 99%